Respuesta :

Answer:

[tex]y=-A+Ce^{kt}[/tex]

Step-by-step explanation:

Let A and k be positive constants

[tex]\frac{dy}{dt} =k(y+A)[/tex]

Here k and A  are constant.

[tex]\frac{dy}{dt} =k(y+A)[/tex]

multiply both sides by dt

[tex]dy=k(y+A)dt[/tex]

[tex]\frac{dy}{y+A} =kdt[/tex]

Integrate on both sides

[tex]ln|y+A|=kt+C[/tex]

Now solve for y. convert it into exponential form

[tex]y+A=e^{kt+C}[/tex]

[tex]y+A=e^{kt}e^C[/tex]

[tex]y+A=Ce^{kt}[/tex]

Subtract A from both sides

[tex]y=-A+Ce^{kt}[/tex]

ACCESS MORE